Indoxyl Sulfate Induces Mesangial Cell Proliferation via the Induction of COX-2 - Shuzhen Li; Sijie Cheng; Zhenzhen Sun; Harr-keshauve Mungun; Wei Gong; Jing Yu; Weiwei Xia; Yue Zhang; Songming Huang; Aihua Zhang; Zhanjun Jia (Mediators of Inflammation)
Indoxyl sulfate (IS) is one of important uremic toxins and is markedly accumulated in the circulation of end stage renal disease (ESRD) patients, which might contribute to the damage of residual nephrons and progressive loss of residual renal function (RRF). Thus this study was undertaken to investigate the role of IS in modulating mesangial cell (MC) proliferation and the underlying mechanism. The proliferation of MCs induced by IS was determined by cell number counting, DNA synthase rate, and cell cycle phase analysis. COX-2 expression was examined by Western blotting and qRT-PCR, and a specific COX-2 inhibitor NS398 was applied to define its role in IS-induced MC proliferation. Following IS treatment, MCs exhibited increased total cell number, DNA synthesis rate, and number of cells in S and G2 phases paralleled with the upregulation of cyclin A2 and cyclin D1. Next, we found an inducible inflammation-related enzyme COX-2 was remarkably enhanced by IS, and the inhibition of COX-2 by NS398 significantly blocked IS-induced MC proliferation in line with a blockade of PGE2 production. These findings indicated that IS could induce MC proliferation via a COX-2-mediated mechanism, providing new insights into the understanding and therapies of progressive loss of RRF in ESRD.